2020
DOI: 10.3390/ijms21072544
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Aspects of the Tumor Microenvironment and Epithelial-Mesenchymal Transition in Gastric Carcinogenesis

Abstract: Infection with Helicobacter pylori, a Gram-negative, microaerophilic pathogen often results in gastric cancer in a subset of affected individuals. This explains why H. pylori is the only bacterium classified as a class I carcinogen by the World Health Organization. Several studies have pinpointed mechanisms by which H. pylori alters signaling pathways in the host cell to cause diseases. In this article, the authors have reviewed 234 studies conducted over a span of 18 years (2002)(2003)(2004)(2005)(2006)(2007)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 231 publications
0
34
0
Order By: Relevance
“…EMT promotes the induction of the cancer stem cell (CSC) phenotype, which facilitates the progression of GC as well as further cellular stemness [ 31 ]. Both in vitro and in vivo studies showed that there is an interplay between EMT and inflammation since EMT facilitates the secondary release of pro-inflammatory cytokines; besides, chronic inflammation occurring in the GC microenvironment also triggers EMT [ 32 , 33 , 34 , 35 ]. Similarly, EMT and reactive oxygen species (ROS) formation are also associated with one another.…”
Section: Epithelial-mesenchymal Transition In Gastric Carcinogenesmentioning
confidence: 99%
“…EMT promotes the induction of the cancer stem cell (CSC) phenotype, which facilitates the progression of GC as well as further cellular stemness [ 31 ]. Both in vitro and in vivo studies showed that there is an interplay between EMT and inflammation since EMT facilitates the secondary release of pro-inflammatory cytokines; besides, chronic inflammation occurring in the GC microenvironment also triggers EMT [ 32 , 33 , 34 , 35 ]. Similarly, EMT and reactive oxygen species (ROS) formation are also associated with one another.…”
Section: Epithelial-mesenchymal Transition In Gastric Carcinogenesmentioning
confidence: 99%
“…Among patients with GC, H. pylori is believed to be the major causation of this malignancy in approximately 92% of patients [ 10 , 11 ]. H. pylori infection enhances the progression of the epithelial–mesenchymal transition (EMT) that induces the oncogenic alterations within the gastric mucosa, constituting one of the hallmarks of gastric carcinogenesis [ 12 , 13 ]. Except for GC, H. pylori is responsible for the induction and progression of other gastrointestinal impairments and diseases, including gastritis, peptic ulcer disease, dyspepsia, or mucosa-associated lymphoid tissue lymphoma (MALT); contrarily, H. pylori is a protective factor against inflammatory bowel disease (IBD) and gastroesophageal reflux disease (GERD) [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric carcinogenesis is a complex, multifactorial process that is primarily stimulated by chronic inflammation (induced by H. pylori infection in the majority of cases); however, other processes such as the epithelial-mesenchymal transition (EMT) or intensified angiogenesis play a crucial role in GC progression [19][20][21][22][23]. Angiogenesis is a physiological process of the formation of the new blood vessels from the already existing ones.…”
Section: Introductionmentioning
confidence: 99%